2021
DOI: 10.1111/pde.14566
|View full text |Cite
|
Sign up to set email alerts
|

Acral Changes in pediatric patients during COVID 19 pandemic: Registry report from the COVID 19 response task force of the society of pediatric dermatology (SPD) and pediatric dermatology research alliance (PeDRA)

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…Also, laboratory investigations were progressively abandoned since all patients tested earlier in the pandemic had not shown any relevant abnormality. Coinciding with the largest registry of pediatric COVID patients published to date by Castello-Socio et al, children with acral pernio-like changes in our series were healthy and all recovered with no short-term sequelae 14. Relapsing of chilblains in otherwise previously healthy children has already been documented.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Also, laboratory investigations were progressively abandoned since all patients tested earlier in the pandemic had not shown any relevant abnormality. Coinciding with the largest registry of pediatric COVID patients published to date by Castello-Socio et al, children with acral pernio-like changes in our series were healthy and all recovered with no short-term sequelae 14. Relapsing of chilblains in otherwise previously healthy children has already been documented.…”
supporting
confidence: 69%
“…Coinciding with the largest registry of pediatric COVID patients published to date by Castello‐Socio et al, children with acral pernio‐like changes in our series were healthy and all recovered with no short‐term sequelae. 14 …”
Section: Discussionmentioning
confidence: 99%
“…In four cases, resolution occurred by day 6, in 47 cases it occurred between 7 to 20 days, and in 80 cases, it occurred after 21 days (11, 13, 17, 19, 22, 23, 25, 26, 28, 29, 33-36, 43, 44, 48, 53). A large study of 378 cases reported lesions resolving an average of 21.6 days after onset, though the median time to resolution was 14 days (11). Other reported outcomes included the following: a majority of 71 cases had a median resolution time of 47 days, 19 cases resolved between 14 and 30 days, 17 cases resolved after a mean of 27 days, eight cases had resolution by a median of 7 days, and seven cases resolved by 8 weeks (12,14,18,37,48).…”
Section: Characteristics Of Patientsmentioning
confidence: 99%
“…The phenotype of cool extremities with pain/swelling, followed by red-violaceous discoloration and finally vesiculation of the toes and fingers were strikingly consistent ( Figure 1 a). Whereas older age was an important risk factor for severe infection, most patients with pernio were young, with a median age of 25 years in an international dermatology registry ( Castelo-Soccio et al 2021 ; Freeman et al 2020 ). Many had close contact with COVID-19 infected individuals, yet nearly all were otherwise healthy and denied typical respiratory manifestations of COVID-19 ( Castelo-Soccio et al 2021 ; Freeman et al 2020 ).…”
mentioning
confidence: 99%
“…Whereas older age was an important risk factor for severe infection, most patients with pernio were young, with a median age of 25 years in an international dermatology registry ( Castelo-Soccio et al 2021 ; Freeman et al 2020 ). Many had close contact with COVID-19 infected individuals, yet nearly all were otherwise healthy and denied typical respiratory manifestations of COVID-19 ( Castelo-Soccio et al 2021 ; Freeman et al 2020 ). The spatial and temporal association between pernio and the COVID-19 pandemic has now been independently observed across multiple countries including Italy, Spain, Germany, the UK, France, and the U.S.
Figure 1 Pandemic-Associated Pernio presentation and histopathology.
…”
mentioning
confidence: 99%